The effect of fiscal incentives on the importation of electric vehicles in Costa Rica - Mora, Mónica (2024)
Starting in 2018, the Costa Rican Government implemented several incentives to promote the adoption of electric vehicles in the country. This study aims to estimate the effect of the fiscal incentives established in the “Law of incentives and promotion for electric transport” on the importation of brand-new electric vehicles between 2010 and 2021, using a negative binomial multiple regression model. The results show that tax exemptions have a positive and significant effect on the importation of electric vehicles; however, this effect is insufficient to meet the decarbonization goals set by the country.